Fumigant and repellent activities of essential oil extracted from Artemisia dubia and its main compounds against two stored product pests. Issue 10 (19th May 2018) - Liang, Jun-Yu; Guo, Shan-Shan; Zhang, Wen-Juan; Geng, Zhu-Feng; Deng, Zhi-Wei; Du, Shu-Shan; Zhang, Ji
Abstract: The major chemical constituents of the essential oil extracted from Artemisia dubia wall. ex Bess. (Family: Asteraceae) were found as terpinolene (19.02%), limonene (17.40%), 2, 5-etheno[4.2.2]propella-3, 7, 9-triene (11.29%), isoelemicin (11.05%) and p -cymene-8-ol (5.93%). Terpinolene and limonene were separated as main components from the essential oil. The essential oil showed fumigant toxicity against Tribolium castaneum and Liposcelis bostrychophila with LC50 values of 49.54 and 0.74 mg/L, respectively. The essential oil and isolated compounds of A. dubia showed repellency activities against both insects. Terpinolene and limonene showed the fumigant toxicity against T. castaneum . Terpinolene showed obvious fumigant toxicity against L. bostrychophila . The results indicated that the essential oil of A. dubia had potential to be developed into natural insecticides for controlling stored product pests. Abstract :